Model Gender Interacts With Expressed Emotion to Enhance Startle: Angry Male and Happy Female Faces Produce the Greatest Potentiation - Åsli, Ole; Øvervoll, Morten (Frontiers in Human Neuroscience, 2020)
Several studies have implied gender differences in startle reaction to emotional facial expressions. However, few studies have been designed to investigate the difference between responding to emotional female vs. male faces, nor gender differences in responses. The present experiment investigated startle EMG responses to a startle probe while viewing pictures of neutral, happy, angry, fearful, and sad facial expressions presented by female and male models. Participants were divided into female and male groups. Results showed that emotional facial expressions interact with model gender to produce startle potentiation to a probe: greater responses were found while viewing angry expressions by male models, and while viewing happy faces by female models. There were no differences in responses between male and female participants. We argue that these findings underline theimportance of controlling for model gender in research using facial expressions as stimuli.